The Baveno VII concept of cirrhosis recompensation. Issue 4 (April 2023) - Reiberger, Thomas; Hofer, Benedikt Silvester
Abstract: Traditionally, the progression from compensated to decompensated cirrhosis has been regarded as a point of no return in the natural history of the disease. However, this point of view is increasingly being challenged by new evidence on disease regression and hepatic recompensation upon suppression/cure of the underlying aetiology. In order to create a uniform definition of recompensated cirrhosis, standardised criteria have been set out by the Baveno VII consensus, which include the removal of the primary aetiological factor, the resolution of any decompensating events and a sustained improvement in hepatic function. Initial insights into the concept of hepatic recompensation come from previous studies, which have demonstrated that a cure/suppression of the underlying aetiology in patients with prior decompensation leads to significant clinical improvements and favourable outcomes and can even enable the delisting of transplant candidates. Nevertheless, future studies are required to shed light on the natural history of hepatic recompensation, assess modifying factors and potential non-invasive biomarkers of recompensation and explore the molecular mechanisms of disease regression.